Freezed Drying of Kelor Leaves Extract (Moringa oleifera Lam.) - Yonathan Tri Atmodjo Reubun; Shirly Kumala; Siswa Setyahadi; Partomuan Simanjuntak (Jurnal Sains dan Kesehatan, 2021)
Moringa oleifera Lam. is a plant that is widely used by people in Indonesia because it is believed to be one of the medicinal plants for various diseases such as diabetes, diuretics, and has the potential to prevent Alzheimer's disease. The purpose of this research is to obtain kelor leaves extract which is more stable in storage and durable, namely by using the freeze drying method, which in this method aims to remove the moisture content in an ingredient or extract. The initial stage of making the extract begins with the extraction of kelor leaves using the maceration method using ethanol as a solvent. The results of maceration are collected and concentrated using a rotary evaporator until a thick extract is obtained and followed by freeze drying which aims to obtain a thick, stable extract. The results showed that 467.12g of kelor leaves extract from 1,000g simplicia was obtained where the yield obtained was 46.71%. the extract yield after freeze drying was 286.03g. After that the extract was tested for phytochemical screening where the results showed that the Moringa leaf extract contained alkaloids, saponins, tannins, phenolics, flavonoids, glycosides, and steroids.